Method for preparing solid polycarbosilane containing active functional groups
By preparing solid polyzirconium carbon-silane containing carbon-carbon double bonds under an inert atmosphere, the problem of insufficient research on solid polycarbosilane modification is solved, the introduction and control of active groups is achieved, and the performance of the material is improved.
Patent Information
- Application Number
- CN202411820579.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-11
AI Technical Summary
The prior art studies on the modification of solid polycarbosilanes, especially the inadequate research on the introduction of active functional groups, limiting its application in high-performance ceramic materials.
Under an inert atmosphere, xylene is used as a solvent, and zirconium dichloride and vinyl magnesium chloride react to form a solid polycarbonsilane containing carbon-carbon double bonds. The active groups are further introduced through the reaction of sodium metal and dimethyl dichlorosilane. After suction filtration, extraction, vacuum drying and high-temperature pretreatment, solid polyzirconium carbosilane containing C=C active functional groups is obtained.
Effectively control the low oxygen content in the product, and control the active group content by adjusting the molar ratio, the synthetic solid polyzirconium carbosilane has wide application prospects and improves the performance of ceramic materials.
Smart Images

Figure CN119798681A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramic materials, and in particular designs a method for preparing solid polycarbosilane containing active functional groups. Background Art
[0002] In recent years, with the rapid development of cutting-edge science and technology in my country's aerospace, nuclear energy, heavy machinery, marine engineering, etc., the requirements for corrosion resistance and high temperature resistance of materials are getting higher and higher. Silicon carbide (SiC) ceramic materials have excellent thermal shock resistance, chemical corrosion resistance, high temperature oxidation resistance, high modulus, low density, small thermal expansion rate and other excellent properties. Compared with other ceramic-based composite materials (Si 3 N 4 , Al 2 O 3 ), it has attracted more and more attention from the public. The preparation processes of SiC ceramic materials mainly include hot pressing sintering, impregnation pyrolysis, reactive infiltration, chemical vapor infiltration, combined process CVI-PIP, CVI-RMI, etc. The impregnation pyrolysis method has the advantages of relatively mild reaction conditions and simple process flow, and has become the mainstream method for preparing SiC ceramic materials.
[0003] The biggest advantage of the synthesis of SiC ceramic materials by the impregnation pyrolysis method is that changing the composition and structure of the precursor can change the composition and yield of the SiC ceramic product. Therefore, the synthesis of the precursor polycarbosilane is the key to producing high-quality and high-yield SiC ceramics. Polycarbosilane mainly includes two types: liquid hyperbranched polycarbosilane and solid Yajima polycarbosilane. There are many reports on the modification of liquid polycarbosilane by grafting different active groups to obtain products with different characteristics. For example, the Chinese patent document with the authorization announcement number CN114573821 uses chloromethyltrichlorosilane and chloromethyl (methyl) dichlorosilane, magnesium as raw materials, tetrahydrofuran and aromatic hydrocarbons as mixed solvents, and obtains liquid polycarbosilane containing carbon-carbon double bonds through Grignard coupling reaction and reduction reaction. In addition, Tian Hua Huang et al. (Chinese Chemical Letters, 2007, 18(6), 754-757) synthesized vinyl-containing hyperbranched liquid polycarbosilane using chloromethyltrichlorosilane, chloromethyl(methyl)dichlorosilane and allyl chloride in a one-pot method.
[0004] In the actual production process, solid polycarbosilane has the advantages of low branching degree, good spinnability, mature process, etc., and occupies an important position in production. However, the modification research related to solid polycarbosilane is very limited and mainly focuses on the introduction of heterogeneous elements (Zr, Hf, Ti, B, etc.). For example, Wang Hao et al. (CN102153760B) disclosed a method for preparing a BC polymer ceramic precursor containing an organic metal M (M is Zr, Hf, Ti), which uses zirconium dichloride (hafnium, titanium) to react with vinyl magnesium chloride or allyl magnesium chloride to generate an organic zirconium (hafnium, titanium) monomer containing a double bond, and then reacts with borane or borazane to generate an organic metal M (M is Zr, Hf, Ti) -BC polymer ceramic precursor. Wang Xiaozhou et al. (CN109054026B) disclosed a method for preparing a HfC-SiC ultra-high temperature ceramic precursor. First, hafnium dichloride, dihaloolefin and magnesium are used to undergo Grignard coupling reaction and condensation reaction in sequence, and then trialkylchloroalkylsilane is added for end-capping reaction to obtain an intermediate product. Finally, the intermediate product is dissolved with polycarbosilane to undergo a hydrosilylation reaction to generate a HfC-SiC ultra-high temperature ceramic precursor. Therefore, it is very necessary to synthesize a solid polycarbosilane containing active functional groups. Summary of the invention
[0005] The purpose of the present invention is to design a new method for preparing solid polycarbosilane containing active functional groups, so as to increase the research on the related modification of solid polycarbosilane and promote the application of solid polycarbosilane containing active functional groups.
[0006] To achieve the above object, the present invention adopts the following technical solutions: A new method for preparing solid polycarbosilane containing active functional groups comprises the following steps: 1) In an inert atmosphere, with xylene as solvent, dichlorozirconocene and vinyl magnesium chloride react at low temperature for 2 to 10 hours, and then keep at room temperature for 5 to 24 hours; 2) The solid-liquid mixture synthesized in step 1) is subjected to suction filtration, extraction and other operations, and the obtained solid product is vacuum dried for 12 to 36 hours; 3) In an inert atmosphere, toluene is used as a solvent, metallic sodium is added to prepare sodium sand, and then the solid product obtained in step 2) and dimethyldichlorosilane are added to react for 5 to 15 hours. After the reaction is completed, the reaction is terminated by ventilation; 4) In an inert atmosphere, the solid-liquid mixture obtained in step 3) is filtered, rotary evaporated and pretreated at high temperature to obtain a solid polyzirconium carbosilane containing a C=C active functional group.
[0007] Preferably, in step 1), the molar ratio of zirconocene dichloride to vinyl magnesium chloride is 0.1 to 2; and the temperature of the low-temperature reaction is -30 to 10°C.
[0008] Preferably, in step 2), the extractant is selected from a mixture of one or more of N,NN-n-octylamine dimethylenephenylphosphonic acid, cyclohexane acid, 2-ethylhexyl phosphate 2-ethylhexyl ester, di(2,4,4-trimethylpentyl) hypophosphorous acid, 2-ethylhexylphosphonic acid mono(2-ethylhexyl) ester and one or more of methyl isobutyl ketone, cyclohexanone, isoamyl alcohol, sec-octanol, and petroleum ether; The vacuum drying temperature is 50 to 150°C.
[0009] Preferably, in step 3), the molar ratio of the solid product obtained in step 2) to dimethyldichlorosilane is 1 / 20 to 1 / 2; 1.1 to 2 times the molar ratio of metallic sodium is added, and sodium sand is prepared by high-temperature stirring; the reaction temperature is 50 to 110° C.; and the ventilation type is selected from one or more of nitrogen, hydrogen, argon, ammonia, helium, etc.
[0010] Preferably, in step 4), the rotary evaporation temperature is 50-180°C; and the high temperature pretreatment temperature is 150-350°C.
[0011] The present invention has the following beneficial effects: The reaction and post-treatment processes of the invention are all carried out under an inert gas atmosphere, and the oxygen content in the product is low; carbon-carbon double bond active groups are introduced by reacting dichlorozirconocene and vinyl magnesium chloride, and theoretically, the content of the introduced vinyl group can be controlled by controlling the molar ratio of the two; the zirconium content in the product can be controlled by adjusting the molar ratio of dichlorozirconocene containing vinyl and dimethyldichlorosilane; and the solid polyzirconium carbosilane containing C=C is synthesized, which has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figure 1 This is the infrared spectrum of the solid polyzirconium carbosilane containing active functional groups prepared in Example 3. DETAILED DESCRIPTION
[0013] The present invention is further described below in conjunction with specific embodiments. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.
[0014] Example 1 1) Under the protection of high-purity nitrogen, add 250 mL of xylene, 17.54 g (0.06 mol) of Cl 2 Cp 2 Zr and 18.75 mL (0.03 mol) ClMgCH=CH 2The reaction was carried out at a speed of 500 rpm and a temperature of -20°C for 4 hours, and then at 20°C for one night. The reaction solution was filtered, and the filtrate was extracted by adding N,NN-n-octylamine dimethylenephenylphosphonic acid and 2-octanol. The extract was filtered to obtain a pale yellow solid product, which was vacuum dried overnight to remove moisture, to obtain 5.79 g of vinylcyclopentadienyl zirconium dichloride.
[0015] 2) Under the protection of high-purity nitrogen, add 150 mL of toluene to a four-necked flask, heat it to 105°C, add 6.36 g of chopped small sodium blocks, keep it warm for 0.5 h, and then stir it quickly to obtain silvery white sodium sand. Lower the temperature to 90°C, add 5.9 g of the dry vinylcyclopentadienyl zirconium dichloride obtained in step 1) and 10 mL of Me 2 Cl 2 Si, after 20 min of reaction, the solution gradually turned into wine red. After stirring for 10 h, NH 3 The reaction was terminated in half an hour. After the solution was cooled, the solution was filtered and the filtrate was evaporated at 150℃ for 1 h to remove the solvent toluene and perform preliminary cross-linking and curing. Liquid nitrogen was cooled to obtain 4.96 g of polyzirconium carbosilane with a yield of about 45.55%. 3.72 g of the solid product was put into a tube furnace and fired at 260℃ for 2 h under argon atmosphere to obtain 3.09 g with a yield of about 83%. Characterization by infrared and other methods proved that the synthesized solid product contained vinyl.
[0016] Example 2 1) Under the protection of high-purity nitrogen, add 250 mL of xylene, 17.54 g (0.06 mol) of Cl 2 Cp 2 Zr and 37.5 mL (0.06 mol) ClMgCH=CH 2 . The reaction was carried out at a speed of 500 rpm and -20°C for 4 hours, and then at room temperature 20°C for one night. The reaction solution was filtered, and 2-ethylhexylphosphonic acid mono(2-ethylhexyl) ester and 2-octanol were added to the filtrate for extraction. The extract was filtered to obtain a pale yellow solid product, which was vacuum dried overnight to remove moisture, to obtain 6.54 g of vinylcyclopentadienyl zirconium dichloride.
[0017] 2) Under the protection of high-purity nitrogen, add 150 mL of toluene to a four-necked flask, heat it to 105°C, add 6.39 g of chopped small sodium blocks, let it stand for 0.5 h, and then stir it quickly to obtain silvery white sodium sand. Lower the temperature to 90°C, add 5.7 g of the dry solid product obtained in step 1) and 10 mL of Me 2 Cl 2 Si, after 20 min of reaction, the solution gradually turned into wine red. After stirring for 10 h, NH3 The reaction was terminated in half an hour. After the solution was cooled, the solution was filtered and the filtrate was evaporated at 150℃ for 1 h to remove the solvent toluene and perform preliminary cross-linking and curing. Liquid nitrogen was cooled to obtain 4.1g of polyzirconium carbosilane with a yield of about 37.65%. 3.25g of the solid product was placed in a tube furnace and fired at 260℃ for 2 h under argon atmosphere to obtain 2.50g with a yield of about 76.9%. Infrared characterization proved that the synthesized solid product contained vinyl.
[0018] Example 3 1) Under the protection of high-purity nitrogen, add 250 mL of xylene, 35 g (0.12 mol) of Cl 2 Cp 2 Zr and 37.5 mL (0.06 mol) ClMgCH=CH 2 . The reaction was carried out at a speed of 500 rpm and -20°C for 4 hours, and then at room temperature 20°C for one night. The reaction solution was filtered, and di(2,4,4-trimethylpentyl) hypophosphorous acid and isoamyl alcohol were added to the filtrate for extraction. The extract was filtered to obtain a pale yellow solid product, which was vacuum dried overnight to remove moisture, to obtain 11.14 g of vinylcyclopentadienyl zirconium dichloride.
[0019] 2) Under the protection of high-purity nitrogen, add 150 mL of toluene to a four-necked flask, heat it to 105°C, add 6.39 g of chopped small sodium blocks, let it stand for 0.5 h, and then stir it quickly to obtain silvery white sodium sand. Lower the temperature to 90°C, add 9.46 g of the dry vinylcyclopentadienyl zirconium dichloride obtained in step 1) and 10 mL of Me 2 Cl 2 Si, after 20 min of reaction, the solution gradually turned into wine red. After stirring for 10 h, NH 3 The reaction was terminated in half an hour. After the solution was cooled, the solution was filtered and the filtrate was evaporated at 150 ° C for 1 h to remove the solvent toluene and perform preliminary cross-linking and curing. Liquid nitrogen was cooled to obtain 6.61g of polyzirconium carbosilane with a yield of about 50.08%. 4.96g of solid product was put into a tube furnace and fired at 260 ° C for 2 h under argon atmosphere to obtain 4.19g with a yield of about 84.47%. Infrared characterization proved that the synthesized solid product contained vinyl (such as Figure 1 as shown).
[0020] Example 4 In order to verify the effect of the extractant on the yield of polyzirconium carbosilane, a comparative experiment was conducted. The experiment was carried out according to the operating conditions in Example 1, except that the extractant was replaced with n-hexane. The following are the experimental steps: 1) Under the protection of high-purity nitrogen, add 250 mL of xylene, 17.54 g (0.06 mol) of Cl 2 Cp 2 Zr and 18.75 mL (0.03 mol) ClMgCH=CH 2 The reaction was carried out at a speed of 500 rpm and a temperature of -20°C for 4 hours, and then at 20°C overnight. The reaction solution was filtered, and the filtrate was extracted with n-hexane. The extract was filtered to obtain a pale yellow solid product, which was vacuum dried overnight to remove moisture, to obtain 3.55 g of vinylcyclopentadienyl zirconium dichloride.
[0021] 2) Under the protection of high-purity nitrogen, add 75 mL of toluene to a four-necked flask, heat it to 105°C, add 3.21 g of chopped small sodium blocks, keep it warm for 0.5 h, and then stir it quickly to obtain silvery white sodium sand. Lower the temperature to 90°C, add 3.0 g of the dry vinylcyclopentadienyl zirconium dichloride obtained in step 1) and 5 mL of Me 2 Cl 2 Si, after 20 min of reaction, the solution gradually turned into wine red. After stirring for 10 h, NH 3 The reaction was terminated in half an hour. After the solution was cooled, the solution was filtered and the filtrate was evaporated at 150°C for 1 h to remove the solvent toluene and perform preliminary cross-linking and curing. Liquid nitrogen was cooled to obtain 1.11 g of polyzirconium carbosilane with a yield of about 18.55%. All the products were placed in a tubular furnace and fired at 260°C for 2 h under an argon atmosphere to obtain 0.41 g with a yield of about 36.9%. Characterization by infrared and other methods proved that the synthesized solid product contained vinyl, but its product yield and ceramic yield were significantly lower than before.
[0022] The above is only a preferred embodiment of the present invention. It should be pointed out that ordinary technicians in this technical field can make several improvements and modifications without departing from the principle of the present invention. These improvements and modifications should also be regarded as the protection scope of the present invention.
Claims
1. A method for preparing a solid polycarbosilane containing active functional groups, characterized in that The following steps are involved: 1) In an inert atmosphere, with toluene as solvent, the metallocene and vinyl magnesium chloride react at low temperature for 2 to 10 hours, and then keep at room temperature for 5 to 24 hours; 2) filtering, extracting and purifying the solid-liquid mixture synthesized in step 1), and drying the obtained solid product for 12 to 36 hours; 3) In an inert atmosphere, add an alkali metal to the solvent, then add the solid product obtained in step 2) and chlorosilane, keep the mixture warm for 5 to 15 hours, and terminate the reaction by ventilation; 4) In an inert atmosphere, the solid-liquid mixture obtained in step 3) is filtered and evaporated to obtain a solid polymetallic carbosilane containing a C=C active functional group.
2. A method for preparing a solid polycarbosilane containing active functional groups according to claim 1, characterized in that: In step 1), the metallocene is dichlorozirconocene, dichlorohafnocene, dichlorotitanocene, or dichloroferrocene.
3. A novel method for preparing solid polycarbosilane containing active functional groups according to claim 1, characterized in that: The low temperature reaction temperature in step 1) is -30 to 10°C.
4. A method for preparing a solid polycarbosilane containing active functional groups according to claim 1, characterized in that: The extractant in step 2) is selected from a mixture of one or more of N,NN-n-octylamine dimethylenephenylphosphonic acid, cyclohexane acid, 2-ethylhexyl phosphate 2-ethylhexyl ester, di(2,4,4-trimethylpentyl) hypophosphorous acid, 2-ethylhexylphosphonic acid mono(2-ethylhexyl) ester and one or more of methyl isobutyl ketone, cyclohexanone, isoamyl alcohol, sec-octanol, and petroleum ether.
5. The method for preparing a solid polycarbosilane containing active functional groups according to claim 1, characterized in that: In step 2), the vacuum drying temperature is 50 to 150°C.
6. A method for preparing a solid polycarbosilane containing active functional groups according to claim 1, characterized in that: In step 3), the molar ratio of the solid product obtained in step 2) to chlorosilane is 1 / 20 to 1 / 2.
7. A method for preparing a solid polycarbosilane containing active functional groups according to claim 1, characterized in that: The alkali metal added in step 3) is potassium, sodium, or lithium, and the molar amount of the alkali metal added is 1.1 to 2 times.
8. The method for preparing a solid polycarbosilane containing active functional groups according to claim 1, characterized in that: In step 3), the reaction temperature is 50-110°C.
9. The method for preparing a solid polycarbosilane containing active functional groups according to claim 1, characterized in that: The ventilation type in step 3) is one or more of nitrogen, hydrogen, argon, ammonia, and helium.
10. The method for preparing a solid polycarbosilane containing active functional groups according to claim 1, characterized in that: In step 4), the rotary evaporation temperature is 50 to 180°C.
Citation Information
Patent Citations
Organometallic polymer ceramic precursor, and preparation method and application thereof
CN102153760B
A method for preparing HfC-SiC ultra-high temperature ceramic precursor
CN109054026B
Organometallic polymer ceramic precursor, and preparation method and application thereof
CN102153760A
Machinable Si / C / Zr ceramic precursor and preparation method thereof
CN103588484A
Metal carbide / silicon carbide multiphase ceramic organic precursor as well as preparation method and application thereof
CN118637922A